Prevalence and factors related to the metabolically obese normalweight (MONW) phenotype: a review - Suliga, Edyta; Głuszek-Osuch, Martyna; Głuszek, Stanisław (Medical Studies/Studia Medyczne, 2023)
The aim of this review was to assess the prevalence and factors related to the metabolic obesity with normal weight (MONW) phenotype. Studies published in English up to December 2021 in the PubMed, Science Direct and Google Scholar databases were searched. The prevalence of MONW is estimated to range from 1.0% to 28.6%, depending on the age of the study participants and the definition of MONW used in the studies. Difficulties in determining the genetic causes of MONW result primarily from the lack of a uniform definition and from the complexity of the disorder. Each component of MONW may be determined by different genes. A person’s lifestyle, in particular their diet, seems to be a significant factor in the development of MONW. Studies have so far been unable to determine the optimal type and duration of dietary intervention needed to improve the metabolic parameters in individuals with MONW.